Combined analysis of the importance of factors in agricultural process management tasks - Gulzira Abdikerimova; Moldir Yessenova; Aizhan Zharkimbekova; Zhanar Beldeubayeva; Aigulim Bayegizova; Nurgul Uzakkyzy; Ainagul Alimagambetova; Gulden Murzabekova (Institute of Advanced Engineering and Science, 2026)
The article presents a combined approach for analyzing the significance of factors in the agro-industrial sector using Shapley additive explanations (SHAP), simple combination, and principal component analysis (PCA)+combination methods. The study addresses the pressing need for efficient agricultural resource management under constrained and changing climatic conditions. The proposed methodology evaluates the impact of various factors on key performance indicators such as yield, income, and operating costs. SHAP analysis identified critical determinants, with